Progressive Dies for L-hanger Ducting (L-HD) Utilizing Low-Carbon Steel SPCC-SD Material: An Experimental and Numerical Analysis - Budiansyah, Ade Cepi; Taufik Ulhakim, Muhamad; Sukarman, Sukarman; Supriyanto, Agus; Amir, Amir; Mulyadi, Dodi; Khoirudin, Khoirudin (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2024)
Industrial developments, especially in the manufacturing and construction sectors, recognize L-hanger ducting as a critical component in HVAC (heating ventilation and air conditioning) ducting systems, which play a role in supporting and stabilizing air ducts. The L-Hanger ducting manufacturing process involves a series of stages, such as shearing, blanking, piercing, trimming, and bending processes. This research focuses on the design and simulation of dies and punches for piercing, blanking, and bending processes using 1.6 mm-thick SPCC-SD material. The aim of this research is to design and analyze progressive dies in order to increase the efficiency of the production process. A comprehensive calculation of the forces involved in the shearing, blanking, piercing, trimming, and bending processes is required in order to predict press machine tonnage requirements to support the production process. This research applies theoretical and numerical validation approaches. Theoretical analysis is used to calculate the overall forces, which are then compared with numerical results and verified through an experimental approach. By understanding and optimizing the design of progressive dies, it is hoped that we can increase the production efficiency of L-hanger Ducting and expand knowledge in the field of metal forming, contributing to the metal forming industry and supporting the development of science.